Population structure of the C hagas disease vector, T riatoma infestans, at the urban–rural interface - Erica A. Foley; Camilo E. Khatchikian; Josephine Hwang; Jenny Ancca‐Juárez; Katty Borrini‐Mayori; Victor R. Quıspe‐Machaca; Michael Z. Levy; Dustin Brisson (Molecular Ecology, 2013)
The increasing rate of biological invasions resulting from human transport or human‐mediated changes to the environment has had devastating ecological and public health consequences. The kissing bug, T riatoma infestans , has dispersed through the P eruvian city of A requipa. The biological invasion of this insect has resulted in a public health crisis, putting thousands of residents of this city at risk of infection by T rypanosoma cruzi and subsequent development of C hagas disease. Here, we show that populations of T ria. infestans in geographically distinct districts within and around this urban centre share a common recent evolutionary history although current gene flow is restricted even between proximal sites. The population structure among the T ria. infestans in different districts is not correlated with the geographical distance between districts. These data suggest that migration among the districts is mediated by factors beyond the short‐range migratory capabilities of T ria. infestans and that human movement has played a significant role in the structuring of the T ria. infestans population in the region. Rapid urbanization across southern S outh A merica will continue to create suitable environments for T ria. infestans, and knowledge of its urban dispersal patterns may play a fundamental role in mitigating human disease risk.

Effects of logging on carbon dynamics of a jack pine forest in Saskatchewan, Canada - Erica A. Howard; Stith T. Gower; Jonathan A. Foley; Christopher J. Kucharik (Global Change Biology, 2004)
We calculated carbon budgets for a chronosequence of harvested jack pine ( Pinus banksiana Lamb.) stands (0‐, 5‐, 10‐, and∼29‐year‐old) and a∼79‐year‐old stand that originated after wildfire. We measured total ecosystem C content (TEC), above‐, and belowground net primary productivity (NPP) for each stand. All values are reported in order for the 0‐, 5‐, 10‐, 29‐, and 79‐year‐old stands, respectively, for May 1999 through April 2000. Total annual NPP (NPP T ) for the stands (Mg C ha −1 yr −1 ±1 SD) was 0.9±0.3, 1.3±0.1, 2.7±0.6, 3.5±0.3, and 1.7±0.4. We correlated periodic soil surface CO 2 fluxes ( R S ) with soil temperature to model annual R S for the stands (Mg C ha −1 yr −1 ±1 SD) as 4.4±0.1, 2.4±0.0, 3.3±0.1, 5.7±0.3, and 3.2±0.2. We estimated net ecosystem productivity (NEP) as NPP T minus R H (where R H was calculated using a Monte Carlo approach as coarse woody debris respiration plus 30–70% of total annual R S ). Excluding C losses during wood processing, NEP (Mg C ha −1 yr −1 ±1 SD) for the stands was estimated to be −1.9±0.7, −0.4±0.6, 0.4±0.9, 0.4±1.0, and −0.2±0.7 (negative values indicate net sources to the atmosphere.) We also calculated NEP values from the changes in TEC among stands. Only the 0‐year‐old stand showed significantly different NEP between the two methods, suggesting a possible mismatch for the chronosequence. The spatial and methodological uncertainties allow us to say little for certain except that the stand becomes a source of C to the atmosphere following logging.